Penjadwalan Tenaga Kerja Satu Shift di PT. XYZ pada Masa Pandemi dengan Metode Algoritma Tibrewala, Philippe & Browne - Corine Destyan Ari Sandy; Yurida Ekawati; Teguh Oktiarso (Teknik Industri Universitas Ma Chung, 2022)
PT XYZ, a ball manufacturer, faced difficulty in setting a labor schedule due to the Pandemi situation, which resulted in limited operational costs and a decline in ball demand. This study aims to solve the problem of regulating the number of workers using the Tibrewala, Philippe & Browne algorithm. The algorithm helps in determining the amount of daily labor required for each production process. The data processing was carried out during Pandemi to determine the effective labor scheduling for all operators. The results showed the need for a reduction in labor, which was achieved by modeling effective labor scheduling within a week period. The cost analysis showed that scheduling could reduce operational costs. Therefore, the study suggested providing training to each operator to work on the entire production process so that the number of operators off is minimized. The algorithm can be beneficial in regulating the workforce in a job order-based company.